Carotenoid and Moisture Stability of Red Fruit (Pandanus conoideus) Oil Powder during Storage - Dewi, Desak Putu Ariska Pradnya; William, William; Tanardi, Samantha; Katherine, Katherine; Mas, Muhammad Abdurrahman; Surjawan, Iwan (Jurnal Gizi dan Pangan, 2023)
The aim of this study was to evaluate the carotenoid and moisture stability of spray-dried and freeze-dried red fruit oil with different wall materials during storage. Red fruit emulsion was prepared by mixing sodium caseinate, maltodextrin and whey protein isolate in different ratios (1:0 (MW1), 3:1 (MW2), 1:3 (MW3) and 0:1 (MW4)), water, and red fruit oil followed by spray or freeze drying. The result showed that the carotenoid content of all samples was stable, but the moisture content changed during storage. Freeze-dried samples showed higher carotenoid and moisture content compared to spray-dried samples throughout the storage.